Peran Media Sosial pada Perilaku Informasi Mahasiswa dalam Menyikapi Isu Kesehatan - Hajar, Herni Wisnumurti; Rachman, Margareta Aulia (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2020)
This article discusses the role of social media towards library and information science (LIS) students’ information behaviour in responding health issues. This is a quantitative study with survey method to collect the data. The survey was distributed to LIS students of Universitas Indonesia in March 2020. The result shows that social media affects students’ information behaviour. The finding also shows that almost all of the students could fulfil their information needs and could distinguish original information and hoaxes on social media, and students did not directly disseminate the information before reading the whole content of the information carefully. Most of the students also checked the information source being used. There is an interesting finding that students preferred to upload personal opinion related to the information they read through their personal social media account than to give opinion on comment box.